Evaluation of Actors Affecting the Time of Residential Building Projects - Jrad, Fayez; Ebrahim, Abeer Ebrahim (Latakia University Journal -Engineering Sciences Series, 2020)
Due to the importance of duration estimation on the success of the project and other important factors, such as cost, also Due to the significant variation between the actual duration of the construction projects and the estimated duration, so It became necessary to identify and evaluate the factors affecting the project duration because it assists developing reliable duration forecasting models and building successful construction project. In this study a questionnaire was designed, to evaluate and rank factors affecting duration of construction projects (Syrian construction projects). A total of 36 effective variables were identified through literature review and interviews, these factors were classified into seven different categories: Client characteristics, Consultant and design parameters, Contractor attributes, Project site, Project characteristics, climate, Other External factors. Statistical analysis is carried out to Confirm responses, by establish an equation which Indicates the relative contribution value for each independent variables (factors) in the dependent variable(duration). A detailed discussion of the results revealed the factors that have the greatest effect on the construction projects duration: Financial ability, no. of basement, Foundation level, Size / gross floor area, Height / no. of stories. نظراً لأهمية تقدير الزمن على نجاح المشروع و على عوامل أخرى أهمها كلفة المشروع، ونظراً للتباين الملحوظ بين الزمن الفعلي لتنفيذ مشاريع التشييد وبين الزمن المقدر، أصبح تحديد وتقييم العوامل التي تؤثر على زمن المشروع من الامور الهامة التي تساعد في تطوير نماذج موثوقة للتنبؤ بالزمن وبالتالي انشاء مشاريع تشييد ناجحة. تمّ في هذه الدراسة تصميم استبيان لتقييم وترتيب العوامل التي تؤثر على زمن مشاريع التشييد (مشاريع الابنية السورية). تضمن الاستبيان 36 متغير يؤثر على زمن المشروع، تمّ الحصول عليها من المقالات والمقابلات وصنّفت تحت سبعة محاور رئيسية: المالك، الاستشاري ومتغيرات التصميم، المقاول، منطقة المشروع، خصائص المشروع، المناخ، عوامل خارجية اخرى. عززت الاستجابات باستخدام التحليل الاحصائي وذلك من خلال بناء معادلة توضح قيمة الاسهام النسبي للمتغيرات المستقلة على المتغير التابع الأساسي وهو الزمن. كشفت مناقشة نتائج الدراسة عن العوامل التي لها أعلى نسبة تأثير على زمن تنفيذ مشاريع الابنية وهي: القدرة المالية للجهة الممولة، عدد الاقبية، عمق التأسيس، عدد الطوابق والمساحة الطابقية.